Expression and clinical significance of Wnt4/β-catenin signaling pathway in glomerular diseases - WU Xiao-zhen; LIU Gang; LIU Man; TAO Lin; JIANG Jin-fang; YANG Xiao-ping (Linchuang shenzangbing zazhi)
Objective To preliminarily investigate the relationship between the expression of wnt4 and β-catenin in the renal glomerulonephritis tissue and renal tubular injury and renal interstitial fibrosis. Methods A total of 56 patients with primary glomerulonephritis and renal biopsy were enrolled in the study. According to tubulointerstitial injury scores, the patients were divided into mild injury group(n=22), moderate injury group(n=18) and severe injury group(n=16), and another 10 patients with normal renal tissues(all from excised normal renal tissues of patients with renal tumor) were chosen as the control group. Immunohistochemistry was used to detect wnt4 and β-catenin in renal tissues in each group. The related clinical indicators were determined at the same time to analyze the relationship between the changes of wnt4 and β-catenin levels and clinical characteristics of the patients. Results Immunohistochemistry showed that, wnt4 and β-catenin were not expressed in renal tissues in the normal control group, but were notably expressed in renal tissues of patients with glomerulonephritis. With the severity of renal interstitial fibrosis, the expression levels of wnt4 and β-catenin exhibited an increasing trend(P<0.05). The expression level of wnt4 in epithelial cells in the renal tubules exhibited positive correlation with β2-microglobin(r=0.29, P<0.05), and negative correlation with eGFR(r=-0.38, P<0.05). Conclusions The expression levels of wnt4 and β-catenin in renal tissue of patients with primary glomerulonephritis with renal interstitial fibrosis are consistent, are both higher than those in normal renal tissue without fibrosis. The wnt4/β-catenin signaling pathway may be involved in the progression of tubulointerstitial fibrosis in glomerulonephritis.